Analisis Perilaku Kecurangan Akademik Pada Mahasiswa Akuntansi Menggunakan Konsep Budaya Hofstede - Wardani, Dewi Kusuma; Nurainun’nisa, Nurainun’nisa (Institut Teknologi dan Sains Mandala, 2024)
This study aims to determine the influence of hofstede culture (power distance, collectivism, avoidance atmosphere, masculinity, short-term orientation, indulgence) on academic fraud behavior. this type of quantitative research and using primary data distributed to students of the Special Region of Yogyakarta with a purposive sampling technique. The samples obtained were 100 respondents. The results of this study are power distance and collectivism have a positive effect on academic fraud behavior, environmental avoidance and indulgence have a negative effect on academic fraud behavior, while masculinity and indulgence have no effect on academic fraud behavior.